Experiment on the convective heat transfer from airflow to skeleton in open-cell porous foams. (March 2017) - Xia, Xin-lin; Chen, Xue; Sun, Chuang; Li, Zhen-huan; Liu, Bo
Highlights: The VHTCs for three porous foams (Cu, Ni and SiC) are experimentally investigated. Seven groups of empirical correlations are compared with the experimental results. A new VHTC correlation with an error of ±40% is proposed for the porous foams. Abstract: In order to understand the heat transfer behavior of forced airflow in open-cell porous foam, a tubular device filled with porous foam is built to conduct the experimental measurement. Three kinds of porous foams of Cu, Ni and SiC with various pore diameters and high porosity from 0.87 to 0.97 are used in the experiment, respectively. The tested sample is heated transiently by the hot airflow with an inlet velocity varying from 2.0 m/s to 9.0 m/s. And the transient temperature data of airflow are measured to determine the volumetric heat transfer coefficients by an inverse analysis. The experimental results are compared with those predicted by seven groups of experimental correlations available at present. Furthermore, an improved correlation of volumetric heat transfer coefficient is presented, which has two independent structure parameters of porosity and pore diameter and is valid for a wide range of Reynolds number 20 ⩽ Red  ⩽ 10 3 . By comparing with all of the available experiment data, the proposed correlation shows an error of ±40%.